PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU SD DIMODERASI KEPEMIMPINAN TRANSFORMASIONAL - Rokhmuji, 12.5202.0122; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze the influence of teachers’ competence and organizational commitment to the performance of primary school teachers that are moderated by transformational leadership. Sources of data are primary data collected directly trough questionnaires from respondents. Measurement of variables using five alternative answers of Likert scale. Based on research result can be summarized that teachers’ competence, organizational commitment, and transformational leadership variables have positive and significant influence towards teachers’ performance. The variable of transformational leadership is not moderating variable of teachers’ competence towards their performance and the variable of transformational leadership is not moderating variable of  organizational commitmet towards teachers’ performance. Keywords : Teachers’ performance, organizational commitment, tranformational leadership and performance.